High Performance Unsymmetrical Two-Phase Induction Motor Drive With Direct Torque Control Based on Unbalanced SVPWM Technique - W. Piyarat; Vijit Kinnares (IEEE Access, 2024)
This paper proposes a high performance unsymmetrical two-phase induction motor drive using unbalanced space vector pulse-width modulation based direct torque control (USVPWM-DTC). The merit of this technique is that both electromagnetic torque and flux are directly controlled without redundancy of the current loop control. A stator flux oriented reference frame is used. PWM signals are generated on the basis of reference voltage vectors. With optimum unbalanced winding voltages, the proposed USVPWM-DTC can overcome a torque pulsation problem resulting from unbalanced parameters of both windings of the motor. Unlike a conventional look up table voltage vector method, the proposed method offers constant switching frequency over a wide range of operating frequency. As a consequence, it is able to cope with several problems such as a stator flux droop problem during sector transition, high current and torque ripple and high noise level. The magnitude of the stator flux is kept constant under various operating conditions and its ripple can also be reduced resulting in performance improvement. The overall drive system is implemented on a real - time DSP TMS320F240 board via dSPACE DS1104 interface card. Furthermore, the proposed system offers more or less fifty percent faster response and almost eighty percent lower torque ripple of electromagnetic torque when compared to a balanced two-phase output space vector pulse width modulation (BSVPWM-DTC) strategy. Experimental results of a 370 W unsymmetrical two-phase induction motor drive under various conditions, such as four quadrant operation, stator flux trajectory, and harmonic spectrum, are presented to demonstrate the viability of the proposed technique which are satisfactory.
Keywords: Sensorless Control of Electric Motors; Electric Motor Design and Analysis; Multilevel Inverters and Converters